Hemodynamic performance of a compact centrifugal left ventricular assist device with fully magnetic levitation under pulsatile operation: An in vitro study. (November 2020) - Wu, Tingting; Lin, Hao; Zhu, Yuxin; Huang, Penghui; Lin, Frank; Chen, Chen; Hsu, Po-Lin
Long-term using continuous flow ventricular assist devices could trigger complications associated with diminished pulsatility, such as valve insufficiency and gastrointestinal bleeding. One feasible solution is to produce pulsatile flow assist with speed regulation in continuous flow ventricular assist devices. A third-generation blood pump with pulsatile operation control algorithm was first characterized alone under pulsatile mode at various speeds, amplitudes, and waveforms. The pump was then incorporated in a Mock circulation system to evaluate in vitro hemodynamic effects when using continuous and different pulsatile operations. Pulsatility was evaluated by surplus hemodynamic energy. Results showed that pulsatile operations provided sufficient hemodynamic assistance and increased pulsatility of the circulatory system (53% increment), the mean aortic pressure (65% increment), and cardiac output (27% increment). The pulsatility of the system under pulsatile operation support was increased 147% compared with continuous operation support. The hemodynamic performance of pulsatile operations is susceptible to phase shifts, which could be a tacking angle for physiological control optimization. This study found third-generation blood pumps using different pulsatile operations for ventricular assistance promising.